2022
DOI: 10.1021/acs.nanolett.1c04315
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Grain Statistics in MOCVD WSe2 through Four-Dimensional Scanning Transmission Electron Microscopy

Abstract: Using four-dimensional scanning transmission electron microscopy, we demonstrate a method to visualize grains and grain boundaries in WSe 2 grown by metal organic chemical vapor deposition (MOCVD) directly onto silicon dioxide. Despite the chemical purity and uniform thickness and texture of the MOCVD-grown WSe 2 , we observe a high density of small grains that corresponds with the overall selenium deficiency we measure through ion beam analysis. Moreover, reconstruction of grain information permits the creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Figure 1(a) demonstrates a strong PL peak at 1.9 eV and was absent of a peak at 1.5 eV which indicated that the sample was primarily monolayer 2H-MoS 2 . RBS was performed to quantify defects and impurities present in the sample as it has been shown to be very sensitive to stoichiometry [10,11,51], as shown in (figure S2, supporting information). Upon analyzing the scattering yield ratio of Mo and S, the Mo:S ratio of the unirradiated sample was obtained to be 1:2.11.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1(a) demonstrates a strong PL peak at 1.9 eV and was absent of a peak at 1.5 eV which indicated that the sample was primarily monolayer 2H-MoS 2 . RBS was performed to quantify defects and impurities present in the sample as it has been shown to be very sensitive to stoichiometry [10,11,51], as shown in (figure S2, supporting information). Upon analyzing the scattering yield ratio of Mo and S, the Mo:S ratio of the unirradiated sample was obtained to be 1:2.11.…”
Section: Resultsmentioning
confidence: 99%
“…We note that additional characterization techniques (e.g., infrared spectroscopy near the CN peak of F 4 -TCNQ) have the potential to yield additional information about the oxidation state of the coating in future work in this field. Together these characterizations and calculations provide strong evidence for a path to high performance thermoelectric nanostructures through the use of in situ organic molecule coatings, which is valuable for future 1D-based thermoelectric and microelectronics applications. , …”
mentioning
confidence: 87%
“…We begin characterization by assessing the general morphology of the nanoribbons via transmission electron microscopy (TEM, image-corrected FEI Titan 80-300, operating at 300 kV), using established experimental and computational postprocessing routines to show that the Bi 2 Te 3 /F 4 -TCNQ nanoribbons are completely coated and that both the Bi 2 Te 3 and Bi 2 Te 3 /F 4 -TCNQ nanoribbons are straight single crystals (Figure a). Atomic force microscopy (AFM, Bruker Dimension Icon) is used to measure rectangular cross sections and suspended lengths of the Bi 2 Te 3 (632 nm × 53 ± 2 nm × 3.89 μm) and the Bi 2 Te 3 /F 4 -TCNQ (794 nm × 269 ± 42 nm × 4.44 μm) core–shell nanoribbons (Figure S1, Supporting Information).…”
mentioning
confidence: 99%
“…Furthermore, 4D-STEM has been applied to moiré heterostructures to unravel the local structural distortions (e.g., in-plane and interlayer strain, twist direction and grain orientations). ,, In particular, interferometric 4D-STEM has been successfully applied to bilayer and trilayer van der Waals materials to measure the local structural distortions and identify the modulation of interlayer spacing as a function of twist angle or stacking order of the constituent layers Figure d highlights the displacement field mapping using interferometric 4D-STEM to study twisted bilayer graphene for twist angles (Θ m ) of 0.63° and 1.37° (the two left panels) as well as maximum amount of induced intralayer strain (right panel) and pronounced lattice distortions localized in saddle-point regions …”
Section: Probing Quantum Materials With Four-dimensional Stem (4d-ste...mentioning
confidence: 99%